2023
DOI: 10.1088/1402-4896/acd5b5
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of TiO2, CuO, and SiO2 nanoparticles addition on the microstructure and mechanical properties of Al-10 wt% Zn alloy

Eman AbdElRhiem,
M M Mostafa,
R H Nada
et al.

Abstract: This paper presents the effects of adding TiO2, CuO, and SiO2 (1 wt%) nanoparticles on the microstructure and mechanical properties of Al-10 wt% Zn alloy. A set of composite alloys was produced by incorporating SiO2, CuO, and TiO2 nanoparticles to the Al-10 wt% Zn alloy. Optical microscope (OM), scanning electron microscope (SEM) fitted with an Energy Dispersive Spectroscope (EDS), and X-ray diffraction (XRD) were used to investigate the microstructure of these alloys. The mechanical properties of the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…The dark gray color indicates Al grains. The silica NS, when combined with the base alloy, forms the aggregated white particles 9 , 10 , as seen in Fig. 3 b.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The dark gray color indicates Al grains. The silica NS, when combined with the base alloy, forms the aggregated white particles 9 , 10 , as seen in Fig. 3 b.…”
Section: Resultsmentioning
confidence: 93%
“…Increasing its characteristics has been challenging due to their applications, including high surface area, well-defined surface properties, chemical, thermal, and water stability, size and shape tunability, and high loading capability 18 . A previous study 9 , 10 indicates that the Al-10 Zn alloy gains microhardness and misconstrues characteristics when ceramic particles' of TiO 2 , SiO 2 , and CuO are added. The presence of CuO nanoparticles enhances the corrosion resistance of the Al-10 Zn alloy.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…5 and 6 . As a result, the strengthening characteristics of the nano-treated A2 increased and hardened than A 1 24 , 30 .…”
Section: Resultsmentioning
confidence: 95%
“…AbdElRhiem et al . 30 studied the Effects of adding TiO 2 , CuO, and SiO 2 nanoparticles on Al–Zn alloy's microstructure and mechanical properties. The study found nanoparticle addition resulted in grain refinement and hardening of the Al–Zn alloy.…”
Section: Introductionmentioning
confidence: 99%